Two new species of Sphaeromopsis (Crustacea: Isopoda: Sphaeromatidae) from the Persian Gulf - Khalaji-Pirbalouty, Valiallah; Wägele, Johann-Wolfgang (Zootaxa, 2009)
Two new species of Sphaeromopsis (Sphaeromatidae: Isopoda) from Iran are described based on light and electronmicroscope study: Sphaeromopsis sarii sp. nov. from the coasts of Kish and Qeshm Islands, and S. persikolpos sp. nov. from Kish Island, Qeshm Islands and the southern coasts of Iran. The two species are sympatric in most areas. Sphaeromopsis sarii is distinct among other species in the genus for having a pleotelson with a faint dorsomedial furrow and a broadly rounded apex. Sphaeromopsis persikolpos sp. nov. is unique for the single suture at either side of the posterior margin of the pleon, a narrow pleotelsonic apex, and the uropodal exopod extensions that reach well beyond the pleotelsonic apex.